2013
DOI: 10.1007/s40119-013-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Versus Beta-Blockers in Patients with Conduction Abnormalities or Left Ventricular Dysfunction Undergoing Cardiac Surgery

Abstract: IntroductionIn patients with conduction abnormalities or left ventricle (LV) dysfunction the use of β-blockers for post cardiac surgery rhythm control is difficult and controversial, with a paucity of information about other drugs such ivabradine used postoperatively. The objective of this study was to compare the efficacy and safety of ivabradine versus metoprolol used perioperatively in cardiac surgery patients with conduction abnormalities or LV systolic dysfunction.MethodsThis was an open-label, randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…15 Recently, Iliuta et al reported a significant reduction of postoperative in-hospital "AF or tachyarrhythmias" by a regimen of perioperative ivabradine combined with metoprolol, versus either drug alone, in a selected cohort of patients undergoing cardiac surgery who had conduction abnormalities (first-degree atrioventricular block or bundle branch block) or left ventricular dysfunction. 16 However, in that study, the difference in the incidence of in-hospital AF between patients who received the combined regimen and those who received metoprolol alone was very small (8.94% vs. 9.66%, respectively, P value not shown for post hoc analysis); therefore, no firm conclusions could be withdrawn. 16 Instead, the current study enrolled a cohort of unselected patients with relatively few exclusion criteria, and adequate left ventricular systolic function.…”
Section: Prevention Of Postoperative Af With Ivabradinementioning
confidence: 81%
See 2 more Smart Citations
“…15 Recently, Iliuta et al reported a significant reduction of postoperative in-hospital "AF or tachyarrhythmias" by a regimen of perioperative ivabradine combined with metoprolol, versus either drug alone, in a selected cohort of patients undergoing cardiac surgery who had conduction abnormalities (first-degree atrioventricular block or bundle branch block) or left ventricular dysfunction. 16 However, in that study, the difference in the incidence of in-hospital AF between patients who received the combined regimen and those who received metoprolol alone was very small (8.94% vs. 9.66%, respectively, P value not shown for post hoc analysis); therefore, no firm conclusions could be withdrawn. 16 Instead, the current study enrolled a cohort of unselected patients with relatively few exclusion criteria, and adequate left ventricular systolic function.…”
Section: Prevention Of Postoperative Af With Ivabradinementioning
confidence: 81%
“…16 However, in that study, the difference in the incidence of in-hospital AF between patients who received the combined regimen and those who received metoprolol alone was very small (8.94% vs. 9.66%, respectively, P value not shown for post hoc analysis); therefore, no firm conclusions could be withdrawn. 16 Instead, the current study enrolled a cohort of unselected patients with relatively few exclusion criteria, and adequate left ventricular systolic function. Moreover, the current study was the first to employ an ambulatory event loop recorder for continuous monitoring and documentation of AF episodes for 15 postoperative days.…”
Section: Prevention Of Postoperative Af With Ivabradinementioning
confidence: 81%
See 1 more Smart Citation
“…The author did not mention about the use of Ivabradine in reducing POAF. Iliuta and Rac-Albu documented that prevention of POAF with combination therapy of metoprolol and ivabradine was more effective than with metoprolol or ivabradine alone during the immediate postoperative management of cardiac surgery patients [2]. Abdel-Salam and Nammas also highlighted that in patients undergoing elective coronary artery bypass grafting, adding ivabradine to β-blockers during the perioperative period was associated with reduced incidence of atrial fibrillation at 30-day follow-up, compared with either medication alone [3].…”
Section: To the Editormentioning
confidence: 99%
“…Moreover, ivabradine is a selective I f current inhibitor that reduces the heart rate without affecting cardiac contractility by selective sinus node inhibition, and has been shown to be cardioprotective in the failing heart [2,3]. Could the author provide relevant information regarding the use of ivabradine in reduction of POAF.…”
Section: To the Editormentioning
confidence: 99%